Effect of formation, ball in play and ball possession on peak demands in elite soccer - Riboli, Andrea; Semeria, Marco; Coratella, Giuseppe; Esposito, Fabio (Biology of Sport, 2021)
This study examined the most demanding passages of match play (MDP) and the effects of playing formation, ball-in-play (BiP) time and ball possession on the 1-min peak (1-min peak ) demand in elite soccer. During 18 official matches, 305 individual samples from 223 Italian Serie A soccer players were collected. MDP and 1-min peak were calculated across playing position (central defenders, wide defenders, central midfielders, wide midfielders, wide forwards and forwards). Maximum relative (m·min -1 ) total distance (TD), high-speed running (HSR), very high-speed running (VHSR), sprint (SPR), acceleration/deceleration (Acc/Dec), estimated metabolic power (Pmet) and high-metabolic load (HML) distance were calculated across different durations (1–5, 10, 90 min) using a rolling method. Additionally, 1-min peak demand was compared across playing formation (3-4-1-2, 3-4-2-1, 3-5-2, 4-3-3, 4-4-2), BiP and ball/no-ball possession cycles. MDP showed large to verylarge [effect-size (ES): 1.20/4.06] differences between 1-min peak vs all durations for each parameter. In 1-min peak , central midfielders and wide midfielders achieved greater TD and HSR (ES:0.43/1.13) while wide midfielders and wide forwards showed greater SPR and Acc/Dec (ES:0.30/1.15) than other positions. For VHSR, SPR and Acc/Dec 1-min peak showed fourfold higher locomotor requirements than 90-min. 1-min peak for Acc/Dec was highest in 4-3-3 for forwards, central and wide midfielders. 1-min peak was lower during peak BiP (BiPpeak) for HSR, VHSR and Acc/Dec (ES: -2.57/-1.42). Comparing with vs without ball possession, BiPpeak was greater (ES: 0.06/1.48) in forwards and wide forwards and lower (ES: -2.12/-0.07) in central defenders and wide defenders. Positional differences in MDP, 1-min peak and BiPpeak were observed. Soccer-specific drills should account for positional differences when conditioning players for the peak demands. This may help practitioners to bridge the training/match gap